UTILISASI PPK II BPJS KESEHATAN: ANALISIS PERBANDINGAN PERILAKU WARGA KOMPLEK PERUMAHAN DAN WARGA PERKAMPUNGAN DI DEPOK - Nia Murniati (Program Pendidikan Vokasi Universitas Indonesia, 2015)
AbstractThe presence of the Social Security Agency (BPJS) actually Health aims to provide a guarantee that participants benefited the maintenance and protection in fulfilling the basic needs of health. Practice, some participants often complain of the long bureaucratic process that must be taken in order to take advantage of these services, particularly for patients at the Hospital (RS). Manage system of care that is applied BPJS require tiered services through Health Care Providers (PPK) Level 1 with a health center, clinic or family doctor. Given, RS is not a big health center that accepts all patients with various forms of health insurance, the participant must be filtered out by primary care in PPK 1. The ideal process is applied BPJS This of course requires a lengthy bureaucracy and a long time. It is often felt to participants BPJS too wordy so make impatient. Although for emergency patient's condition, as the KDP RS Level 2 can accept patients directly without a referral from the KDP 1, but a healthy perception of pain and emergencies often disagree among participants BPJS and RS. This is what often leads to BPJS Health care gap, causing discomfort on both sides. Differences inUtilisasi PPK II BPJS Kesehatan: Analisis Perbandingan Perilaku Warga Komplek Perumahan dan Warga Perkampungan di DepokNia MurniatiVolume 3 Nomor 2, pp.85-9285perception that have the potential to change health behavior BPJS participants in the health facilities be the main focus in this study taking into account the geographical location of residence based on housing estates and villages. Research conducted the survey with tools to guide the interview questionnaire. Subjects were residents of the city of Depok with inclusion criteria who have received health care at the hospital BPJS a maximum of three months. Sampling is done incidentally during one week in Depok City residents (11 districts). The final results of this study are expected to be input for BPJS Health in improving the quality of health services to the community.Keywords: BPJS, 2nd Provider, Utilization.